Personnel protection : security personnel, proven practices - Miller, Jerome; Jones, Radford (Elsevier, 2013)
When it comes to the physical safety of executives, no other preventative measure is more necessary than the proper screening and training of the personnel charged with their protection. In Personnel Protection: Security Personnel presenters Jerome Miller and Radford Jones discuss the critically important task of selecting and training security personnel for executive protection duties. In this seven-minute video presentation of narrated slides, the topics covered include a comparison of contracted and proprietary personnel, the pros and cons of armed versus unarmed personnel, the characteristics of the ideal security person, and the training requirements for hired security personnel. This presentation is one of 11 modules in the Personnel Protection presentation series, which is designed for companies considering an executive security program or for companies with an executive security program already in place.